Critical analysis of research work done by elementary school personnel in the Division of Isabela from 1959 to 1962 - Carino, Teodoro T. 1907- ([Quezon City s.n.], 1963)
This is a study on the extent of research efforts of school personnel through identification and classification of their research works and through the analysis of their evaluation measures.
Thesis (M.Ed.)--University of the Philippines
Keywords: Educational research .